Stafne Bone Defect in Anterior Mandible - Altan Gülay; İşler Sabri Cemil; Özcan İlknur (Balkan Stomatological Society, 2018)
Backround/Aim: Stafne bone cavity which is also known as lingual mandibular bone defect is generally seen in the posterior region of the mandible. Stafne bone defects of the anterior mandible are very rare, with around 50 cases reported in the English literature. They are generally asymptomatic and incidental lesion findings may be diagnosed during a radiographic examination.